2015
DOI: 10.1177/0003489415612801
|View full text |Cite
|
Sign up to set email alerts
|

Improving Quality of Life With Nabilone During Radiotherapy Treatments for Head and Neck Cancers

Abstract: At the dosage used, nabilone was not potent enough to improve the patients' quality of life over placebo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(84 citation statements)
references
References 35 publications
2
69
0
Order By: Relevance
“… 147 Finally, a blinded RCT study examining nabilone in head and neck cancers determined that there was no difference in pain between intervention and placebo groups ( P =0.6048) and that nabilone did not alter the time required for progression of illness by 20% ( P =0.46). 148 …”
Section: Methodsmentioning
confidence: 99%
“… 147 Finally, a blinded RCT study examining nabilone in head and neck cancers determined that there was no difference in pain between intervention and placebo groups ( P =0.6048) and that nabilone did not alter the time required for progression of illness by 20% ( P =0.46). 148 …”
Section: Methodsmentioning
confidence: 99%
“…One clinical trial specifically studied nabilone administration in patients receiving chemotherapy for head and neck carcinomas (n = 65). Compared to the placebo group, nabilone-treated patients did not experience increased quality of life, significant weight change, decreased nausea, or improved appetite during or after chemotherapy [ 160 ]. Another clinical trial recently assessed nabilone’s effect on post-operative nausea and vomiting (PONV) following elective surgery and found no difference in PONV incidence, compared to the placebo [ 161 ].…”
Section: Exploring the Direct Effects Of Cannabinoid Drugs On Bodymentioning
confidence: 99%
“…A recently published placebo-controlled study demonstrated that quality of life for patients with head-and-neck cancers undergoing radiotherapy is not improved with the use of nabilone 51 . The authors postulated that nabilone on its own is not potent enough to affect symptoms.…”
Section: Nausea and Vomitingmentioning
confidence: 99%